MENGUKUR KEBAIKAN MODEL PERSAMAAN STRUKTURAL - Dachlan, Usman (PRESTASI, 2009)
Model with many observed variables in which the number of unique values on covariance matrix are more than the number of parameters being estimated make the model overidentified. The overidentified model constituting general case in structural equation model, nearly always have imperfect fit. Therefore measuring of model fit toward data is necessary to do. The article describe 24 measures of goodness of fit used to assess how fit the model built theoretically can reflect the reality.Keywords: goodness of fit, fit index, structural equation model, fit absolut fit measure, incremental fit measure, parsimonious fit measure.